Penanaman Nilai-Nilai Karakter Berbasis Storytelling Cerita Keagamaan - I Wayan Sutama (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Religious stories that developed in the archipelago, especially the Mahabharata story, became a guide for the people in the life of the nation and state. Education as a means of educating the nation through the mastery of knowledge must be followed by character education so that it can become a whole human being. Religious stories contain various noble values that can strengthen character. This paper aims to understand and analyze the form of character education values contained in Wanaparwa as a form of community adaptability in various conditions faced. This research uses a descriptive qualitative approach with hermenuetic studies. Using literature studies, the results show that the dominant character values found in Wanaparwa stories are truth or honesty, religion, hard work and perseverance. Six value orientations in the Wanaparwa story fulfill Spranger's theory of theoretical value, economic value, aesthetic value, social value, political value, and religious value fulfill the interpretation of the meaning of the Wanaparwa story. Wanaparwa stories are worthy of being adopted by educators (communicators) as media (messages) containing noble character values to be conveyed to students (communicants) through the storytelling method (channel) to strengthen character (effect).